Are El Ninõ and La Nina Phenomena Influenced by Solar Activities ? - Chatief Kunjaya; Iratius Radiman; Zadrach Dupe; Dhani Herdiwidjaja; M. Irfan Hakim (Jurnal Matematika & Sains, 2001)
El Ninõ and La Nina phenomena have caused disasters in many countries. Many million dollar losses has suffered by millions of people in several regions. However the exact cause of the phenomena is still unclear. The Sun plays the central role in determining the earth climate, therefore it is reasonable to think that changes in the Sun behaviour may influence the climate on earth including the El Ninõ and La Nina phenomena. Based on this consideration we tried to find any relationship between the indicator of solar activity, i.e. sunspots, and the indicator of El Ninõ and La Nina phenomena, i.e. Southern Oscilation Index (SOI).